Contactless laser fabrication and propulsion of freely moving structures. (April 2018) - Lazarus, Nathan; Wilson, Adam A.; Smith, Gabriel L.
Abstract: Origami-inspired folding is a well-established method for creating 3D shapes from two dimensional sheets. Here we demonstrate for the first time using a laser to fold, assemble and propel the resulting free-moving part, all without any need for handling. Being able to remotely assemble and move complex parts is an important manufacturing innovation, with potential for controlling doors and latches as well as launching parts off of the build platform without direct assistance. Beginning with only a blank sheet of metal, the parts are first cut and folded using laser forming, where a laser is used to create localized plastic stresses to bend the workpiece. After dropping into place with a final cut, the resulting rotor is actuated with laser ablation propulsion, using a jet of ablated material to apply thrust.